Pengaruh Pengembangan Karir dan Penempatan Kerja Terhadap Prestasi Kerja Karyawan pada PDAM Tirtanadi Provinsi Sumatera Utara - Cut Ermiati; Dita Amanah; Dedy Ansari Harahap; Fitriani Tanjung (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
This study aims to determine the effect of career development and work placement on employee work performance at PDAM Tirtanadi, North Sumatra Province. The population in this study were all employees per division, amounting to 182 employees. From the total population can be determined the number of samples in this study amounted to 65 people. The data analysis technique used is the t-test, f-test, multiple linear regression and determinant coefficient test using SPSS 22. From the calculation results using SPSS shows that there is an influence of career development on employee work performance, there is the influence of work placement on employee performance and there is the influence of career development and work placement on employee performance.